Method and apparatus for saving calibration parameters for a removable cartridge - REIMANN MARK L; BRACKEN ALLEN T; ROCHAT DANIEL D (2004)
An information storage device (10, 510, 610, 710, 810) includes a cradle (12, 512, 612, 712, 812) which can removably receive a cartridge (11, 411, 511, 611, 711) that contains a rotatable hard disk (91, 326-327). A read/write head (107, 331-334) is supported for movement adjacent the disk by a pivotal actuator arm (101). The cradle controls alignment of the head with the disk using feedback servo tracking. Calibration parameters used to perform this tracking, such as servo information or read channel information, may be stored in a special track (414) which is on the disk, and which may be a read-only track. The special track stores a plurality of sets of calibration parameters, each corresponding to a respective combination of a cradle and an environmental characteristic such as temperature. The special track may also be used to store the number of times that the cartridge has been inserted into each of several different cradles, as well as a selected retry method which is more likely than other methods to be successful in recovering data that was subject to errors.